-12=-(2/3)y

Simple and best practice solution for -12=-(2/3)y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=-(2/3)y equation:



-12=-(2/3)y
We move all terms to the left:
-12-(-(2/3)y)=0
Domain of the equation: 3)y)!=0
y!=0/1
y!=0
y∈R
We add all the numbers together, and all the variables
-(-(+2/3)y)-12=0
We multiply all the terms by the denominator
-(-(+2-12*3)y)=0
We calculate terms in parentheses: -(-(+2-12*3)y), so:
-(+2-12*3)y
We add all the numbers together, and all the variables
-(-34)y
We multiply parentheses
34y
Back to the equation:
-(34y)
y=0/-34
y=0
Równanie nie ma rozwiązania

See similar equations:

| |4x-3|=|x+6| | | |4x-3|=|×+6| | | 3x+4=(x-12) | | -12=(-2/3)y | | -14-3+n=26 | | 18x+38=18x+39 | | 4z+4=4 | | 2(7x-2)-3(2x+6)=38 | | (2x+3)=(2x-7) | | -9=-7x+2(x+8) | | 2y-7=-27 | | 2x-16=6x+10 | | 3x+3+4x+3+125=180 | | (3x+2)^2=(x-3)^2 | | -5y+1=36 | | 4n+8(n+1)=−88 | | 189=7(4x+7) | | 2=12m-6m+1 | | 51–3+5k=58 | | −40+5w=4545 | | 8x^2=-5 | | -4-6x=-9x+5 | | 27=11y-2y | | 12(9x–7)=3x–4 | | 5w−3w=8 | | 5x+97-4x=6 | | 6x+1+12=18x+1 | | 4x-2=10+2(x-2) | | x=1500+0.75x | | 4d+2d=6 | | 2/3w-7/5=3/4 | | 0.8n+0.6=42 |

Equations solver categories